Penyuluhan Gerakan Masyarakat Hidup Sehat Berbasis Teknologi di Masa Kenormalan Baru kepada Kader Pemberdayaan Kesejahteraan Keluarga (PKK), Rukun Warga 03, Kelurahan Lenteng Agung, DKI Jakarta - Mubarik Ahmad; Qomariyah Qomariyah; Suhaeri Suhaeri (Lembaga Penelitian Universitas YARSI, 2020)
The spread of Coronavirus 2019 (COVID-19) is increasing towards the community to adjust to new habits. In the new normal era, clean and healthy living habits are essential to be implemented by the community. These healthy living behaviors include wearing masks, washing hands with soap, keeping distance, crowding, eating nutritious food, exercising diligently, etc. However, in reality, there are still people who do not practice this clean and healthy lifestyle. Therefore, we conducted health community movement counseling to PKK cadres, RW 03, Lenteng Agung Village, South Jakarta. This community services activity aims to provide socialization about how to implement a clean and healthy lifestyle in the new era of normality. Also, we introduce how technology can support people to keep their healthy behavior. This outreach was carried out boldly to 20 PKK cadres. We hope that these PKK cadres can become examples and healthy behavior to the surrounding community. The counseling was divided into two sessions: introducing the healthy living movement and the use of technology in the new normal era. Evaluation of activities measured through two questionnaires, namely pre-test, and post-test. The results of the evaluation are increasing knowledge about the healthy life movement and telemedicine. Besides, all participants are willing to adopt a clean and healthy lifestyle after participating in this activity.